The Problem-Based Learning Model and Students' Generic Skills of the Faculty of Teachers Training and Education the Universitas Siliwangi Tasikmalaya on the Animal Structure Course - Mustofa, Romy Faisal; Corebima, A.D.; Suarsini, Endang; Saptasari, Murni (International Journal for Educational and Vocational Studies, 2019)
The aims of this study are to describe the learning process in animal structure courses and learning outcomes obtained by students of Biology Education Study Program, Teachers Training and Education Faculty, Siliwangi University Tasikmalaya after attending lectures. The research method used is survey data collection using a questionnaire. As many as 60 students who have attended and graduated in animal structure lectures in the 4th semester of the 2014/2015 academic year were used as research samples. Samples were taken using simple random sampling technique from a population of 90 students. Then the data obtained is processed using descriptive statistics. The results of the study show that students have an interest in animal structure courses, especially in practical activities. The implementation of learning in animal structure courses has not been carried out optimally. The indication is from the non-socialization of the learning model used by lecturers which has an impact on various generic skills that are not maximally trained and developed.